2017
DOI: 10.19102/icrm.2017.080903
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Cardiac Monitors: Evolution Through Disruption

Abstract: ABSTRACT. Syncope and stroke are commonly seen in clinical practice, and the diagnostic workup is often time-consuming and costly and may increase resource utilization in the health-care system. The use of implantable cardiac monitors (ICMs) in syncope evaluation has been well studied, but their use in cryptogenic stroke evaluation and anticoagulation management in patients with atrial fibrillation (AF) is still emerging. The standard workup of the syncope patient or those at risk for a possible cardioembolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Seminal studies such as RAST (Randomized Assessment of Syncope Trial) [20], PICTURE (Place of Reveal in the Care Pathway and Treatment of Patients with Unexplained Recurrent Syncope) [7], and CRYSTAL-AF[6] trials revealed that ICMs were capable and more successful in detecting AF in patients with syncope (30-36% increased detection rate over a period of ~10 months) and cryptogenic stroke (6-fold increased detection by 12 months) than conventional monitoring. Despite advances in ease-of-implant, remote-monitoring and data collection capabilities, ICMs are not devoid of RWA sensing irregularities [21]. These sensing insu ciencies and related inaccuracies in rhythm detection can delay the diagnosis of arrythmias in syncope and cryptogenic stroke as demonstrated in several small studies reporting the effect of body postures, activity and site of implantation on signal quality received from external or subcutaneous ECG [15,19,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Seminal studies such as RAST (Randomized Assessment of Syncope Trial) [20], PICTURE (Place of Reveal in the Care Pathway and Treatment of Patients with Unexplained Recurrent Syncope) [7], and CRYSTAL-AF[6] trials revealed that ICMs were capable and more successful in detecting AF in patients with syncope (30-36% increased detection rate over a period of ~10 months) and cryptogenic stroke (6-fold increased detection by 12 months) than conventional monitoring. Despite advances in ease-of-implant, remote-monitoring and data collection capabilities, ICMs are not devoid of RWA sensing irregularities [21]. These sensing insu ciencies and related inaccuracies in rhythm detection can delay the diagnosis of arrythmias in syncope and cryptogenic stroke as demonstrated in several small studies reporting the effect of body postures, activity and site of implantation on signal quality received from external or subcutaneous ECG [15,19,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Seminal studies such as RAST (Randomized Assessment of Syncope Trial) [ 20 ], PICTURE (Place of Reveal in the Care Pathway and Treatment of Patients with Unexplained Recurrent Syncope)[ 7 ], and CRYSTAL-AF [ 6 ] trials revealed that ICMs were capable and more successful in detecting AF in patients with syncope (30–36% increased detection rate over a period of ~ 10 months) and cryptogenic stroke (sixfold increased detection by 12 months) than conventional monitoring. Despite advances in ease-of-implant, remote-monitoring and data collection capabilities, ICMs are not devoid of RWA sensing irregularities [ 21 ]. These sensing insufficiencies and related inaccuracies in rhythm detection can delay the diagnosis of arrythmias in syncope and cryptogenic stroke as demonstrated in several small studies reporting the effect of body postures, activity and site of implantation on signal quality received from external or subcutaneous ECG [ 15 , 19 , 22 – 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In specific, we chose the classification of AF in single-lead ECG signals, i.e., the PhysionNet 2017 challenge [38], due to the following aspects. Single-lead ECG data provide a realistic assumption for the input in mobile ECG sensor devices, e.g., smartwatches or implantable cardiac monitors [14]. Here, the attachment of leads (and even the lead positions) is determined by convenience and device form factor, which is viable for daily human activity with minimal compromises.…”
Section: A Algorithm Design Space Explorationmentioning
confidence: 99%
“…for a lifetime of more than one week [13]. In the extreme case, implantable cardiac monitoring systems [14] are expected to operate continuously for 2-3 years with a current budget of around 10 µA [15]. These tight power constraints severely limit what function the cardiac monitoring system is capable of realizing.…”
Section: Introductionmentioning
confidence: 99%